Implementasi Nilai-Nilai Komunikasi Profetik pada Remaja Majelis Rasulllah - Dharmawan, Donny; Wardi, Miftahussa'adah (Bayyin: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The Rasulullah SAW Assembly, commonly called MR, is an assembly which is headquartered on Jl. Cikoko Barat V No. 66 RT. 03/05 Pancoran in South Jakarta and run by Alm. Habib Munzir Al Musawa. This assembly provides religious lessons, which include dhikr and prayer as a means to remember the Creator and His Messenger as well as a means to disseminate Islamic religious knowledge. The Assembly of the Prophet is interesting to study because it describes the success of Prophet Muhammad's prophetic communication, so that his message reaches the present day. In order to find the values of prophetic communication in the Prophet's assembly, researchers carried out research using ethnographic methodology. Researchers are directly involved in the activities of the Prophet's assembly and write down the interactions that exist in the community in order to find the values and meanings stored in the Rasulullah's assembly. This research was conducted on December 12 2022 at the Ar Ridwan Bekasi Islamic boarding school. It was found that most of the youth in the Prophet's assembly implemented prophetic communication values including, shidiq, amanah, tabligh, fathonah in everyday life.